John Grisham's the rainmaker - Grisham, John; Bernstein, Elmer (Widescreen collection, 2010)
A rookie lawyer in over his head on a high-profile case hires a feisty paralawyer who specializes in flunking the bar. Their chances of winning are slim to none until they uncover a trail of corruption.